2016
DOI: 10.1002/pbc.26288
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in pediatric oncology: Lessons learned and next steps

Abstract: The maturation of genomic technologies has enabled new discoveries in disease pathogenesis as well as new approaches to patient care. In pediatric oncology, patients may now receive individualized genomic analysis to identify molecular aberrations of relevance for diagnosis and/or treatment. In this context, several recent clinical studies have begun to explore the feasibility and utility of genomics-driven precision medicine. Here, we review the major developments in this field, discuss current limitations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 113 publications
(185 reference statements)
0
74
0
10
Order By: Relevance
“…Precision medicine, with its focus on matching recommended treatments to specific pathogenic molecular aberrations, is a promising and paradigm-shifting strategy in childhood cancer treatment [1,2]. Access to precision medicine trials may be particularly impactful for paediatric cancer patients with poor-prognosis malignancies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Precision medicine, with its focus on matching recommended treatments to specific pathogenic molecular aberrations, is a promising and paradigm-shifting strategy in childhood cancer treatment [1,2]. Access to precision medicine trials may be particularly impactful for paediatric cancer patients with poor-prognosis malignancies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…108 Furthermore, partly because of their novelty, late effects and toxicities from chimeric antigen receptor T-cell therapy and other targeted therapeutics are poorly understood. 109 Future investigations should explore the barriers to and optimal integration of PPC for these patients and families.…”
Section: The Next Generation Of Ppc Oncology Investigationmentioning
confidence: 99%
“…This constitutes an important contribution to the already published prospective clinical sequencing studies (CSSs) in pediatric oncology. With six published CSSs in pediatric oncology, this manuscript should be considered in light of the general themes emerging in the nascent field of pediatric precision cancer medicine.…”
mentioning
confidence: 99%
“…A recent review nicely summarizes potentially actionable variants most commonly identified by CSSs conducted in pediatric oncology to date. Consistent with some prior studies, the Pincez et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation